Performance of closed-loop power control in DS-CDMA systems in impulsive noise - Kortun, Ayşe; Hocanin, Aykut (My University, 2005)
Accurate power control is an essential requirement in the design of cellular direct sequence code-division multiple-access (DS-CDMA) systems. Effective power control will heavily impact the system capacity. Power control should be able to adjust the power levels of each transmitted signal so that all users will maintain the desired signal-to-noise ratio. In this paper, performance of closed-loop power control is studied in DS-CDMA systems. The performance of the single user and the decorrelating detector by using closed-loop power control algorithm is shown under various channel conditions. The results show that, closed-loop power control improves the performance of decorrelating detector in AWGN and impulsive noise. © 2005 IEEE.
Dürtün gürültülü kanallarda kapali-döngü güç kontrolu ile DD-KBÇE başarimi
IEEE 13th Signal Processing and Communications Applications Conference, SIU 2005 --
Keywords: Closed-loop power control; Direct sequence code-division multiple-access (DS-CDMA) systems; Algorithms; Code division multiple access; Detectors; Impulse noise; Signal receivers; Signal to noise ratio; White noise; Closed loop control systems